A 50 kdyne contusion spinal cord injury with or without the drug SS‐31 was not associated with major changes in muscle mass or gene expression 14 d after injury in young male mice. Issue 4 (21st February 2021) - Graham, Zachary A.; DeBerry, Jennifer J.; Cardozo, Christopher P.; Bamman, Marcas M.
Abstract: Spinal cord injury (SCI) leads to rapid muscle atrophy due to paralysis/paresis and subsequent disuse. SS‐31 is a mitochondrial‐targeting peptide that has shown efficacy in protecting skeletal muscle mass and function in non‐SCI models of muscle wasting. We aimed to determine if SS‐31 could prevent muscle loss after SCI. Male C57BL/6 mice aged 9 weeks underwent sham surgery or 50 kdyne contusion SCI and were administered daily injections of vehicle or 5 mg/kg SS‐31 for 14 d. Both SCI groups had sustained losses in body mass compared to Sham animals and ~10% reductions in gastrocnemius, plantaris and tibialis anterior muscle mass after SCI with no clear effect of SS‐31. Measurements of protein synthesis in the soleus and plantaris were similar among all groups. mRNA expression of atrophy‐associated proinflammatory cytokines was also similar among all groups. There was elevation in MYH7 mRNA and a statistical reduction in MYH2 mRNA expression in the SCI+SS‐31 animals compared to Sham animals. There was an SCI‐induced reduction in mRNA expression of the E3 ligase FBXO32 (MAFbx), but no effect of SS‐31. In summary, a 50 kdyne contusion SCI was able to reduce body mass but was not associated with substantial muscle atrophy or alterations in gene expression profiles associated with muscle health and function 14 d post‐injury. SS‐31 was not associated with protection against SCI‐related changes in body or muscle mass, protein synthesis or gene expression in hindlimb muscles. Abstract : SS‐31 is an efficacious treatment for many pre‐clinical models of muscle disuse. We show that daily injections of SS‐31 were not able to prevent muscle or body mass losses 14 d after an acute contusion SCI in mice.